IMPLEMENTASI VALUE PROPOSITION CANVAS (VPC) SEBAGAI STRATEGI DIGITAL MARKETING PADA BATIK GIRI ALAM - rudi praptomo (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Giri alam is the name of a collective business group that operates in the batik industry sector, which already has a shop that sells traditional gumelem batik and produces handicrafts. The marketing process is only through conventional means, namely in the form of word of mouth marketing promotion, expo-expo held by Banjarnegara and surrounding districts and the Gumelem Ethnic Carnival which is held annually to introduce the Gumelem culture which is also held a batik show involving batik of natural girI. Followed by competitors who sell the typical gumelem batik have also experienced a rapid increase. Lack of adaptation during the COVID-19 pandemic occurred and it is clearly seen on the web that the natural giri batik has not been updated since it was last updated in January. Then related to social media as a promotional media and the land for selling products such as Facebook and Instagram is not maximized right. One of the obstacles to marketing on social media is the content that is less attractive and the quality of the content is not enough. This study uses the Value Proposition Canvas method for evaluation related to business processes and to determine the advantages that Giri Alam has that many other competitors have. Marketing content as a promotional medium that refers to the results of the vpc evaluation. The results of this study are in the form of evaluation of Giri Alam's business processes using vpc and content marketing.